THE IMPACT OF SERVICES QUALITY AND PERCEIVED VALUES ON THE CUSTOMER LOYALTY: MEDIATING ROLE OF CUSTOMER SATISFACTION IN THE TELECOMMUNICATION SERVICE PROVIDERS IN MALAYSIA - shukri, Sakinah mohd; Yajid, Mohd Shukri Ab; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the existing literature is to examine the services quality and perceived value’s impact on the customer loyalty in the Malaysian telecommunication companies. Additional aim of the current study is to inspect the mediating role of customer satisfaction among the nexus of services quality and perceived value and customer loyalty. The measurement of customer loyalty towards a specific telecommunication service provider with the impact of relevant attributes; such as, service quality, perceived value, price and corporate value, in which customer satisfaction is a moderator to identify customer loyalty in a telecommunication service provider’s success. Data was collected from a random sampling of 208 respondents using a questionnaire consisting of 7 demographic questions with open ended questions and 24 items measured on the five point Likert scale. It was found that all the independent variables have a significant effect on Malaysian customer loyalty towards mobile data by telecommunication services providers. Recommendations for future research, marketing implication and limitations of this study are proposed.